Labor Productivity and Access to Markets Matter for Pro-Poor Growth : The 1990s in Burkina Faso and Vietnam - Bernabe, Sabine; Krstic, Gorana (World Bank, Washington, DC, 2018)
Employment is widely perceived as being amongst the most important channels for translating growth into poverty reduction. However there has been limited empirical research to date on the relationship between growth, employment and poverty reduction. This paper focuses on two countries, Burkina Faso and Vietnam, with very distinct patterns of growth and poverty reduction. It examines how employment transmitted growth to the poor during the 1990s in each of these cases and what the role was of specific policies and initial country conditions. In particular, we attempt shed some light on Vietnam’s relative success in terms of pro-poor growth. Understanding these questions will be important in informing the formulation of policies that maximize the participation of the poor in the growth process.This paper is undertaken within the broader framework of the Operationalising Pro-poor Growth (OPPG) study, which is based on 14 country case studies that examine linkages between growth and poverty reduction during the 1990s. The aim of this paper is to supplement the more general labor market analysis contained in the case studies, with a detailed inspection of how employment serves as a transmission channel from growth to poverty reduction.There are two important factors that maximize the effectiveness of employment in transmitting growth to the poor: (1) an increase in labor productivity that is (a) broad based and (b) concentrated in sectors where the poor are disproportionately employed or to which they have access, and (2) strong (domestic and foreign) demand for the goods and services produced by the poor and access to these markets.The paper is organized as follows. It begins with a brief review of what the existing literature tells us regarding the linkages between growth, labor markets and poverty reduction. We then briefly review what can be learned from the 14 OPPG country case studies is this respect. Section four introduces Burkina Faso and Vietnam and provides some basic stylized facts at the beginning of the 1990s, with an aim to set out the initial country conditions. It also highlights how these two countries represent the two extreme patterns of growth and poverty reduction observed in the 14 OPPG country case studies. Section five provides a profile of poverty in the labor market in Burkina Faso and Vietnam, identifying who the poor were at the beginning of the 90’s, which groups faced the highest risks of poverty and how this changed during the 1990s. In section six, examine how labor markets transmitted growth to the poor in Vietnam. It analyzes how growth was reflected in the structure of employment and the extent of underemployment and what the impact was on earnings in sectors where the poor and non-poor were employed. Using panel data we then examine the extent to which the poor in Vietnam were able to benefit from growth by moving out of agriculture and into faster-growing industrial and services sectors. In section seven examines how growth affected the structure of employment and earnings in Burkina Faso during the 1990s. We then briefly analyze how employment affected the distributional pattern of growth in both countries in section eight. Finally, section ten draws some conclusions on how specific policies and initial country conditions affected the way in which employment transmitted growth to the poor in Burkina Faso and Vietnam and what factors can help to explain Vietnam’s relative success in terms of growth and poverty reduction.